Design Estimation of the Amount of Solar Radiation Entering Automobile Glazing - Lenin Rakesh, N.; Anbazhagan, G.; Jayabal, Suriyakumar (International Journal of Psychosocial Rehabilitation, 2019)
The amount of solar radiation entering a closed volume, say a building or an automobile is one of the major challenges to achieve creature comfort inside that closed volume. Automatic air conditioning systems are more common nowadays where sensors are being used to determine the incident solar radiation inside the comfort zone. An attempt is made in this research to replace such costly sensors and complex control logic with a simple algorithm to estimate the amount of solar radiation based on time and geographical data. This calculation of clearsky solar radiation on any receiving surface on earth whether an automobile surface under motion or a static fenestration of a building is derived based on historical data of select geographical locations in the world